Pengaruh Pengetahuan Konsumen dan Gaya Hidup terhadap Keputusan Pembelian Smartphone Merek Samsung di Kota Jambi - Evi Fauzani; Satya Wahyudi; Neng Setiawati (CITRA EKONOMI, 2021)
This study aims to determine the effect of consumer knowledge and lifestyle on purchasing decisions for Samsung brand smartphones in Jambi City partially, and to determine the effect of consumer knowledge and lifestyle on Samsung brand smartphone purchasing decisions in Jambi City simultaneously. This study uses a descriptive quantitative approach with data collection methods through a questionnaire (questionnaire) and documentation. The data obtained in this study were analyzed using multiple linear regression analysis with the SPSS 22 program. The results showed that the calculated F value was 48.774, which means that there is simultaneously an influence on consumer knowledge (X1) and lifestyle (X2) on purchasing decisions for brand smartphones. Samsung in Jambi City. Partially, it can be seen that all independent variables have an effect on purchasing decisions, namely the consumer knowledge variable (X1) of 2.302, which is greater than the t-table value of 1.985 and lifestyle (X2) of 4.837, which is greater than the t-table value of 1.985.